1984
DOI: 10.1002/chin.198442262
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PREPARATION OF BENZYLTHIOPHOSPHONIC ACID DIBROMIDE FROM TRIBENZYL TRITHIOPHOSPHITE AND PHOSPHORUS TRIBROMIDE

Abstract: Tribenzyl‐trithiophosphit (I) und Phosphor‐tribromid (II) reagieren zum gesuchten Dibromid (III), das in das Diamid (IV) übergeführt wird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As should be expected, the reactions of tetrathiophosphates with P(S)C13 occur at higher temperatures than those with P(S)Br3, and they can be completed on heating in a steel tube at 180--220 ~ at temperatures >250 ~ partial resinification of the reaction mixture is observed. It was also revealed that the exchange of thiol groups of tetrathiophosphates can occur stepwise, and at the molar ratio 1 : P(S)CI 3 = 2 : 1, dialkyl trithiochlorophosphates (2) are predominantly formed and isolated in 52--78% yields (Eq. (1), Table 1).…”
mentioning
confidence: 98%
“…As should be expected, the reactions of tetrathiophosphates with P(S)C13 occur at higher temperatures than those with P(S)Br3, and they can be completed on heating in a steel tube at 180--220 ~ at temperatures >250 ~ partial resinification of the reaction mixture is observed. It was also revealed that the exchange of thiol groups of tetrathiophosphates can occur stepwise, and at the molar ratio 1 : P(S)CI 3 = 2 : 1, dialkyl trithiochlorophosphates (2) are predominantly formed and isolated in 52--78% yields (Eq. (1), Table 1).…”
mentioning
confidence: 98%